MAKSIMISASI KEUNTUNGAN PUPUK ORGANIK PADAT DARI LIMBAH TERNAK SAPI PADA KOMUNITAS NATURAL TANI DI DESA OLOBOJU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Sartika, Dewi; Laapo, Alimudin; Afandi, Afandi (AGROTEKBIS, 2018)
This research aimed to determine maximum production, maximum profit and resource allocation used to maximize the benefit of solid organic fertilizers in Farmer Natural community in Oluboju village Sig iBiromaru sub-districtof Sigi Regency. The research was conducted in February-March 2017. Types of data used in this research were primary and secondary data. The primary data obtained by means of observation and direct interviews with the respondents i.e. the Chairman of the Farmers Natural Community, its treasurer, its secretary and one of its members, while the secondary data obtained from several literatures, journals as well as from related agencies that support this research. Analytical tools used in this research were the Linear Programming and Sensitivity analyses. The results showed that the maximum profit obtained from the solidorganic fertilizer businessby the farmer Natural Community was IDR 2,804,144 withthe maximum production of 4,307 kg.The allocation of the resources used to achieve the maximum profits was 22 daily hoursworked per labor, raw materialsof 5,027 kg, and capital of IDR 3,217,659. The production generated by the community was 3,000 kg per month at the rate of raw material used was 3,500 kg per month.